Editorial: Una reflexión desde el confinamiento académico (2020)
In the face of the situation of the Covid-19 pandemic that demands a high level of individual and collective health care in addition to the social confinement demanded by the national states, today more than ever an opportunity is opening up to reflect and to give way to a new sense of conceiving life, to value even more what we have, the simple things of our own daily lives, that landscape that has always been there adorning our experiences, but which is neglected in the eagerness of everyday life and which is now being transformed into something relevant and vital for human beings; Faced with this new dynamic of reality, various changes arise in perceptions, sensations, perspectives, and the way we relate to others. In this sense, education plays a fundamental role toward a path of human recovery that involves dialogue as the only way toward understanding the different situations that arise in academic confinement, such as the lack of connectivity and technological devices in some populations and sectors of society, the psychosocial vulnerability due to the overexposure of information regarding the behavior of the virus in the world through the internet and traditional media. In this sense, the work of education during and after the pandemic is arduous, taking into account economic, social, environmental and emotional factors that in one way or another will transform the traditional way of teaching and learning into new virtual spaces by questioning: will virtuality continue to be an ally, a complement, an alternative, or on the contrary a threat to the face-to-face contact of academic communities? This being the case, the forms of evaluating learning processes will be rethought, academic practices will have to be strengthened based on the construction of the social fabric weakened by the pandemic; the teacher as a social subject, guiding the academic process will tend to demand quality education. This social actor-teacher will see reality in a different way, with new eyes and will put his or her sharpest eye on the social, cultural, environmental, and economic realities of society, taking into account the vulnerable sectors of society. It is there where the call for understanding is awakened, to develop these human values in community, emerging new ideas that will rebuild the ways and dynamics of seeing the world, transcending the individual experience of students, a joint work that focuses the academic community on the development of knowledge. From a spiritual standpoint, study is needed to know how to guide the community with a mature faith where it intervenes in a community life of constant prayer, in that dialogue with God that allows a greater understanding of the adversities suffered by others, regardless of creed. This is precisely what it is about, respecting the different ways of professing faith and transmitting a simple but profound message of the importance of getting closer to God so that He can alleviate the anguish that the world suffers. For this reason, the journal Quaestiones Disputatae of the Department of Humanities and Integral Formation continues to publish analyses and reflections on academic research that has emerged with the highest ethical, scientific and human rigor, with the aim of forming in readers a profound criterion of the different themes addressed in each of the writings.